Penerapan Map-Matching Method pada Aplikasi Mobile Peraturan Zonasi Berdasarkan Rencana Detail Tata Ruang (RDTR) - Aldo Erianda; Fitri Nova (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
According to UU No. 26 of 2007, zoning laws are one of the mechanisms for regulating spatial usage. Supporting tools that are in line with the characteristics and social dynamics of the community are required, specifically through the development of mobile applications, in order to increase public awareness of how space is used and the active participation of the community in monitoring the use of space. The Global Positioning System (GPS) output on an Android mobile device will be compared with the zoning area using this application. Map-Matching, which compares the path geometries of two sources, is the technique employed. using adapting the projected raw position using GPS to the closest zoning segment, the Map-Matching method matches maps. This application is intended to provide information on spatial use zoning regulations, which include clauses governing the use of space and the space envelope that must, may, and may not apply. On the basis of the Payakumbuh City Detailed Spatial Plan (RDTR), application testing was done there. This program uses a map matching method to determine coordinates for spatial use zoning and has a responsive web client server approach